Ionospheric disturbances in a large area of the terrestrial globe by two strong solar flares of September 6, 2017, the strongest space weather events in the last decade - Fagundes, P.R.; Pezzopane, M.; Habarulema, J.B.; Venkatesh, K.; Dias, M.A.L.; Tardelli, A.; de Abreu, A.J.; Pillat, V.G.; Pignalberi, A.; Bolzan, M.J.A.; Ribeiro, B.A.G.; Vieira, F.; et al. (My University, 2020)
On September 6, 2017, the solar active region AR 2673 emitted two solar flares: the first at 08:57 UT (X2.2) and the second at 11:53 UT (X9.3); both were powerful enough to black-out high and low frequency radio waves (where UT is universal time). The X9.3 was the strongest solar flare event in the past decade. In this study, we took the advantage of these two extreme flare events to investigate cor responding effects on the ionosphere using multi-instrument observations from magnetometers, Global Positioning System – Total Elec tron content (GPS-TEC) receivers, ionosondes and Swarm satellites over a large geographical extent covering South American, African and European sectors. During the X2.2 flare, European and African sectors were sunlit and during X9.3 European, African, and South American sectors were sunlit and exposed to the solar flare radiation. During the X2.2 flare, there was an ionosonde blackout for a dura tion of about 45 min, while during the X9.3 flare this blackout lasted for 1 h and 30 min. The blackout are seen over a large global extent which demonstrates the severity of solar flare events in disrupting the radio communication. The horizontal component of Earth’s geo magnetic field has shown ripples and enhancements during these flare events. The ionospheric Vertical Total Electron Content (VTEC) showed a positive phase along with an intensification of the Equatorial Ionization Anomaly (EIA) over the South American and African sectors. The dynamical and physical processes associated with the TEC and EIA variabilities due to solar flare are discussed. 2020 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: F-Region; Ionosphere; Solar flare; EIA